Discounting and the market valuation of defined benefit pensions. (4th October 2021) - Breedon, Francis; Larcher, Luca
Abstract: We investigate how defined benefit pension (DB) schemes of the Financial Times Stock Exchange (FTSE) firms are valued by the equity market, focusing on how future liabilities are discounted (because UK data allows us to estimate the duration of pension liabilities fairly accurately). Our primary sample of FTSE 100 constituents includes mostly large DB sponsors with mature schemes, primarily closed to new entrants but still active for current employees. We find that equity market valuation of pension liabilities is consistent with discounting without allowing for credit risk, thus incorporating a valuation closer to their settlement value. This differs from the approach used in published accounts for which IAS 19 (and SFAS no. 158, its US equivalent) allows for discounting with a corporate bond yield. The difference is significant, as credit‐risk‐free discounting would decrease the reported value of FTSE 100 firms by about 7%.